Hungary: Hungaricums of the Family Law Policy - Sápi, Edit (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
It is now considered a fact that Europe, including Central Europe, is facing an ageing society. One of the main indicators of this issue is the decrease in the number of births and the increase in the number of older adults. Several countries are attempting to implement related measures to encourage an increase in the number of births. This chapter reviews and summarises these comprehensive family policy measures. In addition, it presents the specific legal institutions and legal provisions in the Family Law Book of Hungary’s Civil Code that may affect the safety of family life.Keywords: Hungarian family policy, ageing society, Central Europe, birth rate, demographic challenge, legal response